MICROFOCUSED ULTRASOUND ASSOCIATION X SCULPTRA A DESCRIPTIVE OBSERVATIONAL STUDY - Viana Cavalcate Nobre, Rayana; Regina Veronezi, Lauscea; Viviane Nogueira, Márcia; Rabelo Lima Barbosa, Chystianne; Rodrigues Ribeiro, Henrique; Lemos Maia, Juliana; Mendonça de Oliveira, Larissa; Elayne Silva Montezuma, Gina; Januzzi Santos, Marcelo (Health and Society, 2023)
The search for a healthier way of aging reflects the growing understanding that longevity alone is not enough. Advances in aesthetic technologies have brought with them the increasing use of ultrasound-emitting equipment to deliver thermal energy not only to the superficial dermis but also to the deep dermal connective tissue. Studying the application of microfocused ultrasound associated with Sculptra® Poly-L-lactic Acid (Galderma - Switzerland) is justifiable, as it directly addresses the growing concerns related to skin aging at all ages. The objective of this work is to evaluate the effectiveness of the combination of microfocused ultrasound and Sculptra® in a case study. Materials and methods: case study that demonstrates a stereophotogrammetric evaluation using the Vectra H2 Software (Canfield – USA) whose clinical case is a facial clinical association of Microfocused Ultrasound with Poly-L-lactic Acid. The case was carried out on patient KBS, brown, 61 years old. The specific combination of Microfocused Ultrasound and Poly-L-lactic Acid, as collagen biostimulators, represents a promising approach in the treatment of sagging. Stereophotogrammetric analysis with 3D Vectra H2 software offers an objective, visually detailed and scientifically validated assessment of the results of this therapeutic combination. The inclusion of measurements both at baseline and 120 and 240 days after treatment allows for a more complete understanding of the results, evolution and durability of effects.